1995
DOI: 10.1038/hdy.1995.133
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus heterozygosity and size: a test of hypotheses using triploid Mytilus edulis

Abstract: Cohorts of meiosis I and meiosis II induced triploid Mytilus edulis were produced from mass matings in the laboratory and reared alongside normal diploid cohorts during 1990 and 1991. Diploid cohorts generally exhibited a significant positive correlation between multilocus heterozygosity and size. This correlation was absent or much more weakly expressed in cohorts.of triploid mussels and this supports the 'associative overdominance' hypothesis rather than the 'direct involvement' hypothesis as the major expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Methods inhibiting polar body expulsion using cytochalasin B or 6-DMAP (Gérard et al 1999) were developed first for triploid induction and allowed diploid -triploid comparisons to be made (e.g. for oysters see Allen & Downing 1986, Kesarcodi-Watson et al 2001, Mallia et al 2006; for mussels see Beaumont et al 1995, Brake et al 2004; for clams see Guo & Allen 1994a; for scallops see Tabarini 1984, Racotta et al 2008. More recently, the production of tetraploid oysters (Guo & Allen 1994b, Eudeline et al 2000a, McCombie et al 2005b) has led to a large increase in the aquaculture of triploid oysters produced by mating tetraploid with diploid parents .…”
Section: Introductionmentioning
confidence: 99%
“…Methods inhibiting polar body expulsion using cytochalasin B or 6-DMAP (Gérard et al 1999) were developed first for triploid induction and allowed diploid -triploid comparisons to be made (e.g. for oysters see Allen & Downing 1986, Kesarcodi-Watson et al 2001, Mallia et al 2006; for mussels see Beaumont et al 1995, Brake et al 2004; for clams see Guo & Allen 1994a; for scallops see Tabarini 1984, Racotta et al 2008. More recently, the production of tetraploid oysters (Guo & Allen 1994b, Eudeline et al 2000a, McCombie et al 2005b) has led to a large increase in the aquaculture of triploid oysters produced by mating tetraploid with diploid parents .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are few studies where a heterozygosity genic deficiency could be mostly discarded, these studies support the associative overdominance hyphothesis. The study of Beaumont, Fairbrother & Hoare (1995) on diploid and triploid mussels supports the associative overdominance hypothesis to explain the correlation of allozyme heterozygosity and growth found in spite the absence of genic heterozygote deficiency or inbreeding. Finally, the results obtained on marine bivalves by Zouros, Romero-Dorey & Mallet (1988) and Leberg, Smith & Rhodes (1990) on deer foetuses are compatible with the simultaneous existence of general and local effects.…”
Section: Discussionmentioning
confidence: 56%
“…In a recent study, Hawkins et al (1994) have indeed found that meiosis I triploids of the European oyster Ostrea edulis outperformed meiosis II triploids, but the latter were not statistically different from normal diploids. Beaumont et al (1995) did not observe size differences at the juvenile stage between triploids and diploids in the blue mussel Mytilus edulis and, in particular, found no indication that tri-allelic triploids were different from di-allelic ones for several enzyme loci. The progressive haploidization hypothesis may account for some of these observations, but the available evidence is not enough for a critical evaluation of the various versions of genetic hypotheses.…”
Section: (Iii) Extension To Polyploidsmentioning
confidence: 63%